The Expression Status of G Protein-Coupled Receptor GPR30 Is Associated with the Clinical Characteristics of Endometriosis. (November 2013) - Yuguchi, Hiroko; Tanabe, Akiko; Hayashi, Atsushi; Tanaka, Yoshimichi; Okuda, Kiyoji; Yamashita, Yoshiki; Terai, Yoshito; Ohmichi, Masahide
<x xml:space="preserve">Abstract</x> Introduction. GPR30 is a seven-transmembrane G protein-coupled estrogen receptor that regulates endometrial cellular responses to estrogen. GPR30 is often highly expressed in cancer cells from aggressive tumors. The aim of this study was to evaluate the expression patterns of GPR30 in endometriosis during medical treatment. Patients. A total of 38 females, 28 patients with endometriosis and 10 patients with leiomyoma who underwent laparoscopic surgery were included this study. Intervention. Eutopic endometrial tissue sampling from women without endometriosis and ectopic endometrial tissue sampling from women with endometriosis. Main Outcome Measure. A quantitative real-time polymerase chain reaction analysis of the mRNA expression in eutopic and ectopic endometrial tissues with or without GnRH agonist treatment. The expression of GPR30 was confirmed by immunohistochemistry. Results. There was an increased level of GPR30 mRNA in eutopic endometrium during the proliferative phase, whereas higher expression was observed in the ectopic endometrium during the secretory phase. Increased GPR30 mRNA was observed in ectopic endometrium in comparison to eutopic endometrium. GnRH agonist treatment before laparoscopic surgery decreased GPR30 mRNA in ectopic endometrium. The immunohistochemical analysis also revealed that GPR30 was strongly expressed in epithelial cells in ectopic endometrium, whereas GnRH agonist treatment decreased the GPR30 expression. Conclusion. High levels of GPR30 expression can play an important role in the progression of endometriosis.